Public policies for education completion: The case of Argentina's Fines Plan - Viego, Valentina (Education Policy Analysis Archives, 2015)
In 2008 the Federal Council of Education ordered the creation of Completion of Primary and Secondary Education for Youth and Adults Plan (locally known as Fines). The purpose of the program is to offer young people and adults a plan aimed to basic education completion. The paper analyzes the design and implementation of the plan considering educational aspects, working conditions of teachers and the resources provided by the national government and the provinces to meet the goals. The review of norms and acts that normalize the operation of Fines and interviews with participating actors suggest that the initiative is based on underfunding, it poses the gradual substitution of the previous system working with adult education and strengthens an education system sustained with precarious learning and teachers.